The determinants of urban concentration - Karsten Junius (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
Urban concentration differs across countries. One determinant of these differences is economic development, which first increases and subsequently decreases urban concentration. I condition the degree of urban concentration on the potential of countries to develop a balanced urban system. These conditions are approximated by the land area, population density and density of the transportation system, which all decrease urban concentration. It is also found that countries with a long independent urban history have lower degrees of urban concentration than countries with a recent colonial past. Furthermore, I assess the impact of some historic variables and historic patterns of urban concentration on current patterns of concentration.
Keywords: R11; R12; 330; Industrialization; Urban Concentration; Economic Development; Urbanisierung; Regionale Konzentration; Entwicklung; Bevölkerungsdichte; Verkehrsinfrastruktur; Wirtschaftsliberalismus; Schätzung; Welt; Siedlung